Diversity of ants and mites in the diet of the Brazilian frog Chiasmocleis leucosticta (Anura: Microhylidae) - Lopes, Mariana S.; Bovendorp, Ricardo S.; Moraes, Gilberto José de; Percequillo, Alexandre Reis; Bertoluci, Jaime (Biota Neotropica, 2017)
Abstract We describe here the diet of the microhylid frog Chiasmocleis leucosticta based on the stomach contents of 72 individuals (47 males and 25 females) collected in pitfall traps at the Reserva Florestal de Morro Grande, state of São Paulo, southeastern Brazil. We identified 1,981 food items distributed in 13 prey categories of arthropods, mainly ants, mites and collembolans. Formicidae was the most abundant and frequent prey category, including 16 genera from seven subfamilies, and data on ant availability in the habitat suggest that C. leucosticta selects ants actively. The second main prey category was Acari, predominantly represented by mites of the suborder Oribatida. This is the first work identifying mites to the family level in the diet of a Microhylidae. There was no statistical difference between males and females regarding diet composition.